POPULARITAS DAN KOMODIFIKASI KONTEN TELEVISI DI ERA DIGITAL - Aditianingrum, Kurnia Alysia; Adnan, Ricardi (Jurnal Analisa Sosiologi, 2023)
Television often commodifies content in nowadays’ digital era, especially those related to the personal life of celebrities. In fact, this violates the norms stated in the provisions of P3SPS Chapter 9th article 13th paragraph 2nd regarding Respect for Privacy Rights and has the potential to make audiences ignore social realities that exist in society. This study uses a qualitative descriptive approach which aims to show the commodification of the personal life content of artists on television in the digital era by using the concept of struggle for recognition and institutions from market from meaning. Through literature review by collecting observational data on television and YouTube content with the theme of the artist's personal life, as well as secondary data in the form of online news searches, documents and journals to complement the findings. The results of the study show that the greater the ability of each actor to become a prosumer and reach the popularity, the greater the opportunity to commodify personal content facilitated by the broadcasting industry and other institutions for economic purposes. This can be seen in various television stations which commodify the content of the personal lives of artists by showing wedding processions, 7 monthly processions, and aqiqah with quite high intensity in 2021, as well as other artists' daily activities in infotainment by combining content from the artist's Youtube channel. This phenomenon shifts existing values which makes the KPI institution soften in responding to it. Keywords: Broadcast Industry, Commodification, Digital, Prosumer   AbstrakTelevisi kerap melakukan komodifikasi konten di era digital saat ini, terlebih yang berkaitan dengan kehidupan pribadi. Padahal, hal ini melanggar norma yang tercantum dalam ketentuan P3SPS Bab 9 pasal 13 ayat 2 mengenai Penghormatan Terhadap Hak Privasi dan berpotensi membuat khalayak mengabaikan realitas sosial yang ada di masyarakat. Penelitian ini menggunakan pendekatan deskriptif kualitatif yang bertujuan menunjukkan komodifikasi konten kehidupan pribadi artis dalam televisi di era digital dengan menggunakan konsep struggle for recognition dan institusi dari market from meaning. Melalui kajian kepustakaan dengan pengumpulan data observasi konten televisi dan Youtube yang bertema kehidupan pribadi artis, serta data sekunder berupa penelusuran berita daring, dokumen, dan jurnal untuk melengkapi temuan. Hasil penelitian menunjukkan bahwa semakin besar kemampuan setiap aktor untuk menjadi prosumer dan mendulang popularitas, semakin besar pula peluang untuk mengkomodifikasikan konten pribadi yang difasilitasi oleh industri penyiaran beserta institusi lainnya dengan tujuan ekonomi. Hal ini tampak pada berbagai stasiun televisi yang mengkomodifikasikan konten kehidupan pribadi para artis dengan menayangkan prosesi pernikahan, prosesi 7 bulanan, serta aqiqah dengan intensitas cukup tinggi di tahun 2021, juga aktivitas harian artis lainnya di infotainment dengan menggabungkan konten dari channel Youtube artis. Fenomena ini menggeser nilai yang ada yang membuat melunaknya institusi KPI dalam menyikapinya. Kata Kunci: Industri Penyiaran, Komodifikasi, Digitali, Prosumer